Communities of Interpretation: The Case of the Qur’an (American Journal of Islam and Society, 2016)
This article discusses “Communities of the Qur’an,” a conference,public talk, and forthcoming book that will examine the Qur’an’s“communities of interpretation.” They are represented by ten worldrenownedacademics and leaders from the Sunni, Shi‘i, and Ahmadicommunities; reformist LGBT, feminist, African American, andQur’an-only groups; as well as non-Muslims like the Bahais. In thisbrief paper, I discuss their nature, engagements with the Qur’an asa text or an experience, and the challenges they face in the twentyfirstcentury.